2009
DOI: 10.1111/j.1460-2695.2008.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

The strength of annealed, heat‐strengthened and fully tempered float glass

Abstract: A B S T R A C T In the last two decades architectural glass has made an enormous leap from a secondary material to a material that combines structural and cladding roles. The structural role is a new and problematic one. In contrast to most other engineering materials the strength of glass is not a material parameter but a parameter dependent on processing quality and damage to the glass surface. There is also no real agreement on how strong glass is. There is a concept Euronorm for structural glass that has v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…For the more common float glass this is more complicated. Results of bending experiments by various authors suggest that the processing and specimen size influence the results and suggest systematic data deviation from the Weibull statistic distribution [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the more common float glass this is more complicated. Results of bending experiments by various authors suggest that the processing and specimen size influence the results and suggest systematic data deviation from the Weibull statistic distribution [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…For the more common float glass this is more complicated. Results of bending experiments by various authors suggest that the processing and specimen size influence the results and suggest systematic data deviation from the Weibull statistic distribution [3][4][5].A likely explanation for this is that the usual processing of float glass results in multiple types of defects which provides a multilinear Weibull plot [6,7].To investigate this systematically it was decided to look in more depth at the effect of processing on float glass strength. The initial step, which is described in this paper, deals with the effect of cutting and breaking quality on the strength of processed float glass.…”
mentioning
confidence: 99%
“…(8) in one form or another (prEN 16612:2013). A number of studies, however, have indicated that the Weibull distribution does not provide a superior fit compared with a lognormal or normal distribution (Lü 1997;Calderone et al 2001;Veer et al 2009;Huerta et al 2011;Kinsella and Persson 2016). It has been noted that the estimated value of the Weibull shape parameter varies quite significantly from one sample to another in experiments (Ritter et al 1985;Carre 1996;Huerta et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…First, glass fracture statistics tend to produce bimodalities in the probability plots according to e.g. Veer et al (2009). In fact, the experiment considered in Sect.…”
Section: Dual Population Modelmentioning
confidence: 99%
See 1 more Smart Citation